1985
DOI: 10.1136/jech.39.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory conditions: effect of housing and other factors.

Abstract: SUMMARY The public health movement has been concerned with the relation between housing and health for well over a century. Nevertheless the Black Report still identified housing as one of the major causes of ill-health and suggested, on one indicator at least, that council housing is the least healthy form of tenure. An exploratory study concerning housing and health in a north eastern local authority area is described. It was found that smoking, work experience, and age were the most important determinants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…13 A number of researchers have suggested a link between the frequency of home moves and the development of respiratory conditions or infections. 15,36,37 Our findings reinforce previous work in illustrating that moving home frequently presents an increased risk of PPH for asthma and ear, nose, and throat infections. We also found that increased residential mobility resulted in an increased risk of PPH for convulsions and epilepsy, dehydration and gastroenteritis, and influenza/pneumonia.…”
Section: Discussionsupporting
confidence: 87%
“…13 A number of researchers have suggested a link between the frequency of home moves and the development of respiratory conditions or infections. 15,36,37 Our findings reinforce previous work in illustrating that moving home frequently presents an increased risk of PPH for asthma and ear, nose, and throat infections. We also found that increased residential mobility resulted in an increased risk of PPH for convulsions and epilepsy, dehydration and gastroenteritis, and influenza/pneumonia.…”
Section: Discussionsupporting
confidence: 87%
“…Household crowding has been found to cause increased incidence of respiratory infections, but whether this is associated with development of COPD in adulthood is unsettled. In a British study, people in areas of bad housing were found to report more respiratory symptoms, and flats were found to be worse than houses [17]. A Danish study focusing on housing found that smoking-adjusted FEV1 was reduced by 10 mL?yr of living -1 without central heating [18].…”
Section: Discussionmentioning
confidence: 99%
“…10 Poor-quality housing and dampness in particular are believed to cause respiratory ill health. 11,12 Allergic reactions to house dust mites [13][14][15] or airborne spores of molds [16][17][18] are plausible mechanisms for a causal relationship between damp housing conditions and respiratory symptoms. Associations among reported dampness, molds, and respiratory symptoms in children have been reported.…”
Section: Introductionmentioning
confidence: 99%